Differences in the composition of soils under open and canopy conditions at two sites close-in to the great Canadian oil sands operation, Fort McMurray, Alberta - Baker, J. (1980)
Soils sampled at Sites 1 and 2, 2.3 and 5.3 km south of the Great Canadian Oil Sands (GCOS) plant, Fort McMurray, respectively were found to differ statistically with reference to several macronutrients. Soils under cover of a canopy and those in open areas differed considerably with respect to soil nutrients and pH. Differences in nutrient concentrations under open versus covered soils probably are due mainly to effects of the canopy; however, this may not fully explain soil sulphur and titanium concentrations. Jack pine foliage sampled at Site 1 was more concentrated in S than that sampled at Site 2, suggesting the possibility that atmospheric sulphur may have played a role. Other foliar nutrient differences more likely are the result of other or natural phenomena. To date, despite the higher S concentrations in both jack pine foliage and soils under the canopy at Site 1, there is no conclusive evidence that atmospheric pollutants emitted as a result of the overall exploration operation have as yet altered the existing soil nutrient regime of the study area, or are responsible for differences observed between the two sites.